Ekstrak Akar Purwoceng sebagai neuroprotektan Terhadap Model Stroke pada Tikus: Memori Spasial, Jumlah Sel Piramidal, Ekspresi SOD1 dan SOD2 - Munawaroh, Fauziyatul; Efiyanti, Christy; Utami, Putri; Dewi, Trisni; Batubara, Irmanida (Jurnal Tumbuhan Obat Indonesia, 2024)
Stroke due to cerebral ischemia is one of the leading causes of disability worldwide. Animal models of cerebral ischemia that is often used is Global Cerebral Ischemia (GCI). In GCI, the hippocampus is the most susceptible to neuronal cell death. Complications that occur after ischemia are due to increased oxidative stress. Some compounds in purwoceng are reported to have antioxidant activity which oxidative stress have not been studied in the GCI model stroke. This study aims to examine the effect of purwoceng extract on a stroke model (GCI) as a neuroprotective agent in the prevention of stroke complications that have not been previously studied. 25 rats with a stroke model were given purwoceng root extract with 3 doses (20, 30, and 40mg/kg BW) orally for three days. The mice were then tested for memory with the Morriz Water Maze (MWM) test; then histopathological analysis of pyramidal cells in the hippocampus and the expression of SOD1 and SOD2 genes was analyzed using RT-PCR. The MWM test showed that the memory results at the dose of 20mg/kg BW were better than that of the GCI group (p=0.0384), and the PCR of SOD2 showed improvement at the dose of 20mg/kg BW (p=0.0171). No significant difference in histopathological analysis and SOD1 mRNA expression across group. The administration of purwoceng root extract at a dose of 20 mg/kg BW had the effect of improving memory and SOD2 expression in GCI model rats